2015
DOI: 10.1124/dmd.115.065938
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Has No Clinically Meaningful Effect on the Pharmacokinetics of the Organic Anion Transporting Polypeptide 1B1 and Cytochrome P450 3A4 Substrate Simvastatin

Abstract: Simvastatin and clopidogrel are commonly used together in the treatment of cardiovascular diseases. Organic anion transporting polypeptide (OATP) 1B1 activity markedly affects the hepatic uptake of simvastatin acid, whereas both simvastatin and simvastatin acid are sensitive to changes in cytochrome P450 3A4 activity. Clopidogrel and its metabolites inhibit OATP1B1 and CYP3A4 in vitro. We studied the effect of clopidogrel on the pharmacokinetics of simvastatin in a randomized crossover study. Twelve healthy vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 38 publications
(52 reference statements)
1
31
0
Order By: Relevance
“…Our result is consistent with the lack of clinically relevant OATP1B1-mediated DDI of clopidogrel with simvastatin and fluvastatin, although it causes an increase in the AUC of repaglinide (5.0-fold) mainly via the inhibition of CYP2C8 by clopidogrel acyl-b-glucuronide (Ayalasomayajula et al, 2007;Tornio et al, 2014;Itkonen et al, 2015). A clinical study found that a single oral dose of 300 mg clopidogrel increased the AUC of rosuvastatin (1.7-fold) in patients with coronary heart disease (Pinheiro et al, 2012).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our result is consistent with the lack of clinically relevant OATP1B1-mediated DDI of clopidogrel with simvastatin and fluvastatin, although it causes an increase in the AUC of repaglinide (5.0-fold) mainly via the inhibition of CYP2C8 by clopidogrel acyl-b-glucuronide (Ayalasomayajula et al, 2007;Tornio et al, 2014;Itkonen et al, 2015). A clinical study found that a single oral dose of 300 mg clopidogrel increased the AUC of rosuvastatin (1.7-fold) in patients with coronary heart disease (Pinheiro et al, 2012).…”
Section: Discussionsupporting
confidence: 73%
“…However, the clopidogrel-mediated DDIs with OATP1B1 or OATP1B1/CYPs substrates are not consistent. Although rosuvastatin, simvastatin, and fluvastatin are substrates of OATP1B1, clopidogrel increased the plasma concentration of rosuvastatin (1.7-fold for AUC) but did not change those of simvastatin and fluvastatin (Ayalasomayajula et al, 2007;Pinheiro et al, 2012;Itkonen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Both cerivastatin and repaglinide are substrates for CYP2C8, as well as for CYP3A4 and OATP1B1 (Mück, 1998;Kantola et al, 1999;Backman et al, 2002;Wang et al, 2002;Niemi et al, 2003;Kajosaari et al, 2005;Niemi et al, 2005). According to a recent study, clopidogrel does not cause a significant change in the disposition of simvastatin or its active acid form in humans (Itkonen et al, 2015). As simvastatin is among the most sensitive drugs to changes in CYP3A4 and OATP1B1 activity (Neuvonen et al, 1998;Backman et al, 2000;Ichimaru et al, 2001;Prueksaritanont et al, 2003;Pasanen et al, 2006;Niemi et al, 2011), clopidogrel is unlikely to have a clinically relevant effect on CYP3A4 or OATP1B1 activity (Itkonen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As simvastatin is among the most sensitive drugs to changes in CYP3A4 and OATP1B1 activity (Neuvonen et al, 1998;Backman et al, 2000;Ichimaru et al, 2001;Prueksaritanont et al, 2003;Pasanen et al, 2006;Niemi et al, 2011), clopidogrel is unlikely to have a clinically relevant effect on CYP3A4 or OATP1B1 activity (Itkonen et al, 2015). These findings indicate that inhibition of CYP2C8 by clopidogrel acyl-b-D-glucuronide is the main mechanism of the clopidogrel-cerivastatin and clopidogrel-repaglinide interactions (Floyd et al, 2012;Tornio et al, 2014;Itkonen et al, 2015). This conclusion is also supported by a recent case report, which suggests that clopidogrel significantly reduces the metabolic clearance of the CYP2C8 substrate anticancer agent paclitaxel (Bergmann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation